(untitled) (Journal of actual problems of jurisprudence, 2021)
This article examines problems regarding the application of the law of unrecognized states in private international law. The urgency of this problem lies in the possibility of applying the law of unrecognized states in the field of private international law, given their unresolved status in accordance with international public law. Despite the fact that these entities cover all the requirements provided for in the 1933 Montevideo Convention on the Rights and Duties of the State, they are still not given the full opportunity to function as full-fledged states. The existence of unrecognized states is a big obstacle in the settlement of many disputes. The status of these associations is difficult to determine by the current norms of international public law, however, in the light of this problem, questions are asked in the field of private international law: should states apply the law of unrecognized states. This article will be considered using a general and comparative legal analysis that will provide answers about the possibility of applying the law of unrecognized states. In the conclusion of this article, a set of recommendations for solving this problem is offered, which will help find solutions for the application of the law of unrecognized states in private international law. Keywords: unrecognized states, the law of unrecognized states, application of foreign law, recognition of foreign documents, conflict of laws, state recognition.